2009
DOI: 10.1136/jech.2008.079715
|View full text |Cite
|
Sign up to set email alerts
|

Does socioeconomic status fully mediate the effect of ethnicity on the health of Roma people in Hungary?

Abstract: Background: Several models have been proposed to explain the association between ethnicity and health. It was investigated whether the association between Roma ethnicity and health is fully mediated by socioeconomic status in Hungary. Methods: Comparative health interview surveys were performed in 2003-04 on representative samples of the Hungarian population and inhabitants of Roma settlements. Logistic regression models were applied to study whether the relationship between Roma ethnicity and health is fully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
0
7

Year Published

2010
2010
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 28 publications
8
74
0
7
Order By: Relevance
“…In general, life expectancy in Roma men and women is 10-15 years shorter than in their non-Roma counterparts from the same region, they have a higher prevalence of different diseases such as coronary artery disease, obesity, hyperlipidaemia, and diabetes mellitus compared with the majority population, and experience more frequent occurrence of health problems/complaints (4,(17)(18)(19)(20). Published studies on the health of Roma are often fragmentary and burdened with methodological problems (3,21,22). According to the European Foundation for the Improvement of Living and Working Conditions, living in housing of poor quality has also a negative impact on Roma health: they have an increased risk of disability, chronic illness and being overweight.…”
Section: Introductionmentioning
confidence: 99%
“…In general, life expectancy in Roma men and women is 10-15 years shorter than in their non-Roma counterparts from the same region, they have a higher prevalence of different diseases such as coronary artery disease, obesity, hyperlipidaemia, and diabetes mellitus compared with the majority population, and experience more frequent occurrence of health problems/complaints (4,(17)(18)(19)(20). Published studies on the health of Roma are often fragmentary and burdened with methodological problems (3,21,22). According to the European Foundation for the Improvement of Living and Working Conditions, living in housing of poor quality has also a negative impact on Roma health: they have an increased risk of disability, chronic illness and being overweight.…”
Section: Introductionmentioning
confidence: 99%
“…Like these studies, further articles published about Roma living in Europe and especially in Central-Eastern Europe also emphasized these populations' poor health resulting from low socioeconomic status (SES), severe social exclusion, unfavourable behavioural patterns, and the environment, all of which could influence birth outcome (8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…18 At the other end, one study provided no details on the defi nition or methods used to identify a specifi c and rarely studied ethnic group; the Roma people of Europe. 54 We found that only 19.6% of authors provided any discussion regarding the limits of using an ethnic or racial categorization. Of those mentioned, these limits were related to issues of group aggregation (e.g., Asian), generalization outside a given territory or state, generalization related to generational status, racial or ethnic misclassifi cation by individuals or health-care providers, arbitrary measures of novel concepts (e.g.…”
Section: Transparency In Methods and Limits Of Classifi Cationmentioning
confidence: 87%